2003
DOI: 10.1063/1.1609234
|View full text |Cite
|
Sign up to set email alerts
|

Young modulus dependence of nanoscopic friction coefficient in hard coatings

Abstract: We present an atomic force microscope study of nanoscopic sliding friction on diamond, diamond-like carbon, and on three CrN thin films with varying hardness obtained by different growth temperatures. For the CrN films, we show that the changes in the friction coefficient can be traced back to variations of the Young modulus. More generally, we show for all samples investigated and in wearless regime, that the nanoscopic friction coefficient is directly linked to the Young modulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 17 publications
(19 reference statements)
3
33
0
Order By: Relevance
“…It is well known that elastically hard solids tend to exhibit smaller sliding friction than (elastically) soft materials [8]. One extreme example is diamond, which under normal circumstances exhibits very low kinetic friction coefficient, of the order of 0.01, when diamond is sliding on diamond.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that elastically hard solids tend to exhibit smaller sliding friction than (elastically) soft materials [8]. One extreme example is diamond, which under normal circumstances exhibits very low kinetic friction coefficient, of the order of 0.01, when diamond is sliding on diamond.…”
Section: Introductionmentioning
confidence: 99%
“…From this figure, it is seen that the friction coefficient decreases nonlinearly with increasing temperature. At high temperature, desorption of water from environmental humidity leads to decrease the meniscus force (which is a major contributor to the adhesive force), and the friction between the AFM tip and the investigated sample (Bhushan 2005;Kapila et al 2006;Liu and Bhushan 2003;Riedo and Brune 2003). As the temperature is increased, the force needed to shear the contacting junctions where adhesion occurs decreases, respectively, and the tip jump the surface potential barriers more easily, resulting in lower shear strength and hence lower friction force and friction coefficient (Kapila et al 2006).…”
Section: Variation Of Adhesion and Friction Forces As A Function Of Tmentioning
confidence: 99%
“…To estimate the friction coefficient, friction force should be divided by the sum of applied normal load F AFM (given by the bending of AFM probe) and intrinsic adhesive force F adh (Bhushan 2003;Kapila et al 2006;Riedo and Brune 2003;Schonherr et al 2008).…”
Section: Variation Of Adhesion and Friction Forces As A Function Of Tmentioning
confidence: 99%
“…Owing to the large surface to volume ratio, friction at contact is of fundamental importance for reliability of micro/nano-devices, such as NEMS and hard-disk drives [6,7]. It has been reported that there was a transition of frictional shear strength, decreasing by almost one order of magnitude as the contact radii shrank into the nanoscale range [8].…”
Section: Introductionmentioning
confidence: 99%